DNA Damage Response Signaling Triggers Nuclear Localization of the Chicken Anemia Virus Protein Apoptin - Kucharski, Thomas J. (American Society for Microbiology, 2011)
The chicken anemia virus (CAV) protein Apoptin is a small, 13.6-kDa protein that has the intriguing activity of inducing G(2)/M arrest and apoptosis specifically in cancer cells by a mechanism that is independent of p53. The activity of Apoptin is regulated at the level of localization. Whereas Apoptin is cytoplasmic in primary cells and does not affect cell growth, in transformed cells it localizes to the nucleus, where it induces apoptosis. The properties of cancer cells that are responsible for activating the proapoptotic activities of Apoptin remain unclear. In the current study, we show that DNA damage response (DDR) signaling is required to induce Apoptin nuclear localization in primary cells. Induction of DNA damage in combination with Apoptin expression was able to induce apoptosis in primary cells. Conversely, chemical or RNA interference (RNAi) inhibition of DDR signaling by ATM and DNA-dependent protein kinase (DNA-PK) was sufficient to cause Apoptin to localize in the cytoplasm of transformed cells. Furthermore, the nucleocytoplasmic shuttling activity of Apoptin is required for DDR-induced changes in localization. Interestingly, nuclear localization of Apoptin in primary cells was able to inhibit the formation of DNA damage foci containing 53BP1. Apoptin has been shown to bind and inhibit the anaphase-promoting complex/cyclosome (APC/C). We observe that Apoptin is able to inhibit formation of DNA damage foci by targeting the APC/C-associated factor MDC1 for degradation. We suggest that these results may point to a novel mechanism of DDR inhibition during viral infection.